Computational Mechanics of the Classical Guitar - Bader, Rolf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
This book performs a state-of-the-art finite-difference calculation of the complete geometry of the classical guitar as a time-stepping application. It provides insight into the overall behaviour as well as the finite structure mechanisms of this musical instrument. Fundamental problems of coupling, nonlinearities, noise or time reversion, complex modelling solutions, and modern signal processing tools are discussed. Also musicologists, musicians or instrument builders can find explanations and may also be inspired by aspects of musical timbre, the sounding and time-dependent qualities of the different guitar parts. The work helps to suggest new geometrical and timbral solutions in modern guitar performance. Rolf Bader studied systematic musicology, physics, ethnology, and music history at the University of Hamburg, Germany. He currently works and performs as a guitarist in the field of jazz, modern classical music and improvisation. His work focuses on the musical timbre in acoustics, music psychology and physiology. Since 2002 he has been teaching acoustics, finite-element and finite-difference methods at the University of Hamburg and has been working on several projects in musical acoustics. His ethnological work on the music and cultural interchange in Southeast Asia, especially about Bali and Nepal includes cultural and historical but also acoustical aspects.
The Musical Transient-Modeling Software MTMS Developed for this Study -- Continuous and Discrete Mechanics -- Studies of the Guitar To Date -- The Discrete Guitar Model -- Bending, Damping and Coupling -- Results -- Summary and Outlook.
Keywords: Engineering; Music; Acoustics; Statistical physics; Dynamical systems; Applied mathematics; Engineering mathematics; Mechanics; Mechanics, Applied; Vibration; Dynamics; Engineering; Theoretical and Applied Mechanics; Vibration, Dynamical Systems, Control; Music; Appl.Mathematics/Computational Methods of Engineering; Acoustics; Statistical Physics, Dynamical Systems and Complexity; Electronic books